An analysis on the purpose of offering Mandarin in Malaysian public universities and its commencement / Hoe Foo Terng … [et al.] - Hoe, Foo Terng; Liaw, Shun Chone; Lim, Teck Heng; Er, Ann Nah; Marimuthu, Rasaya (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
In this study, the purpose of conducting Mandarin classes at Malaysian public universities is discussed. This is done from the perspective of the university. In this qualitative study, applied literature review and expert interviews were employed to report the development of Mandarin teaching in all the Malaysian public universities. Interviewees and respondents of this study were heads of the respective Chinese department/unit, Mandarin lecturers or language teachers, and some part-time teachers of the public universities. Some part-time teachers were selected because a few of the public universities have no permanent Mandarin teachers or lecturers. The respondents of this study were firstly given the interview questions via e-mail. This is followed by an appointment to carry out a phone interview with each respondent. After a transcription of each phone interview was completed, a copy of the transcription was given to the respective respondent to verify. Each respondent was given the freedom to make amendments to any errors made. The final version of each interview was used in the final analysis. The findings showed that 60.9 percent of the Mandarin classes in the 20 public universities were established with only one purpose. The remaining 39.1 percent have two purposes. On another note, 67.8 percent of the universities took the initiatives to offer Mandarin classes in order to prepare their graduates for employment. The commencement and development of Mandarin classes in Malaysia public universities is closely related to China’s economy. With China still rising as one of the world’s largest economy body, the Malaysian public universities will continue to encourage their students to take up Mandarin so as to produce graduates who could excel in future endeavour